DIVERSION IN THE JUVENILE JUSTICE SYSTEM: A REVIEW OF IMPLEMENTATION AND CHALLENGES - Atika, Nur; Nuh, Ahmad; Salam, Abdul; Safaruddin, Safaruddin (PT. Altin Riset Publishing, 2025)
This research aims to find out the implementation and challenges of diversion. In this study, an empirical method is used. The primary and secondary data obtained are analyzed using a qualitative method, namely analyzing data related to the problem being researched, then selecting based on logical thinking. The results of this study show that: The implementation of diversion in the juvenile criminal justice system in Indonesia has a very important role in protecting children from the adverse effects of the judicial process. Despite the many challenges faced in its implementation, with improvements in terms of training law enforcement officials, and rehabilitation facilities, and increasing public awareness, diversion can be a more effective and profitable solution for children facing the law. Efforts to improve and pay greater attention to children's rights in the criminal justice system are expected to realize a fairer, more humane justice system and support child rehabilitation.